Second Thoughts on Free Riding - Ulrik H. Nielsen; Jean-Robert Tyran; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2013)
We use the strategy method to classify subjects into cooperator types in a large-scale online Public Goods Game and find that free riders spend more time on making their decisions than conditional cooperators and other cooperator types. This result is robust to reversing the framing of the game and is not driven by free riders lacking cognitive ability, confusion, or natural swiftness in responding. Our results suggest that conditional cooperation serves as a norm and that free riders need time to resolve a moral dilemma.
Keywords: C70; C90; D03; 330; Response Time; Free Riding; Public Goods; Experiment